2021
DOI: 10.1016/j.jconrel.2020.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Learning from past failures: Challenges with monoclonal antibody therapies for COVID-19

Abstract: COVID-19, the disease caused by infection with SARS-CoV-2, requires urgent development of therapeutic interventions. Due to their safety, specificity, and potential for rapid advancement into the clinic, monoclonal antibodies (mAbs) represent a highly promising class of antiviral or anti-inflammatory agents. Herein, by analyzing prior efforts to advance antiviral mAbs for other acute respiratory infections (ARIs) , we highlight the challenges faced by mAb-based imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 89 publications
3
20
0
Order By: Relevance
“…Remarkably, the ability of 76clAbs to recognize an essential and conserved spike antigenic epitope translates into the neutralization of the delta variant and the so far identified VBMs, some of which known to drive escape of approved and investigational mAbs (22). The single chain antibodies here proposed for nasal or lung topical delivery might overcome limitations of parenteral mAbs aimed for a systemic passive immunization (23). Developed as a complementary approach to the existing vaccination and passive systemic immunization, that do not induce a robust mucosal defense (24), this class of antibodies may contribute to halt the SARS-CoV-2 infection at its early stages.…”
Section: Regarding the Biochemical Properties Of 76clabs Size Exclusion Chromatography (Sec-hplc)mentioning
confidence: 99%
“…Remarkably, the ability of 76clAbs to recognize an essential and conserved spike antigenic epitope translates into the neutralization of the delta variant and the so far identified VBMs, some of which known to drive escape of approved and investigational mAbs (22). The single chain antibodies here proposed for nasal or lung topical delivery might overcome limitations of parenteral mAbs aimed for a systemic passive immunization (23). Developed as a complementary approach to the existing vaccination and passive systemic immunization, that do not induce a robust mucosal defense (24), this class of antibodies may contribute to halt the SARS-CoV-2 infection at its early stages.…”
Section: Regarding the Biochemical Properties Of 76clabs Size Exclusion Chromatography (Sec-hplc)mentioning
confidence: 99%
“…However, it has been reported that the treatment with CCP has little effect on the outcome of the disease in hospitalized patients [37][38][39][40]. Likewise, mAb has limited efficacy once patients are hospitalized, but there is clinical benefit when mAb are administered early in the course of disease [41][42][43][44]. Preliminary results suggest that hIG may act in a similar way, that is, by preventing patient hospitalization [45].…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation mAb candidates are in preclinical and clinical trials some demonstrating promise as a superior drug, e.g., nirsevimab [79,80]. mAbs including motavizumab and suptavumab (REGN2222) have recently failed to reach clinical trial endpoints [81]. Small-and large-molecule drugs in RSV therapeutic development have recently been reviewed [82].…”
Section: Rsv Epidemiologymentioning
confidence: 99%